From the security of supply to energy independence in urban and regional environments in Mexico, transition towards a paradigm (2015)
If national energy security is being violated within some Latin American countries from the high costs of electricity and irregular supply of natural gas bill, among other factors, which are undermining the efficient operation of enterprises and institutions; therefore imposes ask: Is the concept of the prevailing energy security, characterized to ensure adequate energy supply from a macroeconomic perspective, is cracking? In particular, is it possible to refer to the concept of Energy Autonomy as a new option in the process of energy transition to renewable energy? Given this increasingly common scenario of uncertainty in energy security in urban and regional environments are we facing a transition of paradigms? In this sense, the purpose of this study is to elucidate the two concepts, in order to show that organizational efforts, both private and public-through-renewable energy options are achieving energy self-sufficiency in some cities and regions of Mexico, I could be foreshadowing a new pattern of energy independence in these territorial spaces.